Implementasi Supervisi Manajerial dalam Meningkatkan Kinerja Guru di MTSN 3 Sumedang - Linda Tazkiyatul Munawaroh; Muhammad Alamsyah; Muhammad Fikri Shidiq; Muhammad Amar Khana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
Managerial supervision has an important role in improving the quality of education in Madrasah Tsanawiyah. Target managerial supervision includes two kinds of the principal as manager education, and the 8 national education standards in school. By functionit known that the role of a superintendent as managerial supervisor is as a consultant, managing, fostering, and accompanies in dealing with common problems on managerial governance in school. The research was conducted at MTsN 3 Sumedang. The method usedin this research is using a qualitative approach. Data collection procedures were carried out through observation, interviews, and documentation studies. The results of the study show that: 1) The implementation program of managerial supervision in MTsN 3Sumedang by the principal aligns with the stages of planning, implementation, assessment, reporting, and follow-up. 2) The managerial supervision of the principal of MTsN 3 Sumedang has adhered to the 8 national education standards. 3) Managerial supervision in 3 Sumedang serves as the foundation for maintaining the quality of education in MTsN 3 Sumedang and its development plan.